SPECTRAL VARIATION OF Be HERBIG STARS - Pavlova, L. A.; Kondratyeva, L. N.; Valiullin, R. R. (Одеські астрономічні публікації, 2007)
We researched the characteristic time scales and amplitudes of the variability of Hα emission and intrinsic polarization of Be Herbig stars: VY Mon, LkHα215 and HD 259431. The change of Hα profiles as PCyg - PCygIII - single-peaked was revealed in the spectrum of VY Mon. Such transformation is widely accepted to be formed in stellar wind. The double Hα profiles of LkHα215 and HD 259431 reflect the presence of the rotating disk-like envelope with signs of outflow and infall of matter.